Perancangan Media Pembelajaran Informatika Kelas x Menggunakan Smart Apps Creator di SMA Negeri 5 Bukittinggi - Edwar Adrian Putra Adam; Hari Antoni Musril; Riri Okra; Sarwo Derta (Jurnal Media Infotama, 2024)
The technology available today is developing so rapidly, supported by adequate and quality human resources. Every element of human life, including education, has felt the benefits of this technological development. Learners must go through a process to achieve educational goals, namely learning by following a series of anticipated learning processes by a teacher to foster an interesting learning atmosphere, such as through the use of learning media. Based on the interview results with an informatics subject teacher for the tenth grade at SMA Negeri 5 Bukittinggi, there is still a need for the use of textbooks and student worksheets (LKS) in the informatics learning process. Additionally, in delivering teaching materials, it is still not optimal and still relies on the lecture method. As a result, students tend to have difficulty receiving the material presented and talk to each other while the teacher is explaining, because the teacher has not utilized the available technology to the fullest, including the blackboard. Consequently, the learning becomes less effective. The research design for informatics learning media using Smart Apps Creator at SMA Negeri 5 Bukittinggi used the Research and Development (R&D) method. The system development model used the development model. The analysis phase, design phase, development phase, and implementation phase are the three phases that form the Hannafin and Peck learning design model. Validity, practicality, and effectiveness tests were used to evaluate the product in this study. The author conducted product testing, and the results showed that the product passed the validity test by three experts with a score of 0.78, the practicality test by three practitioners with a score of 0.73 in the high category, and the effectiveness test by 30 students and one informatics teacher with a score of 0.90 in the very high effectiveness category